KEBIJAKAN PEMERINTAH DAERAH DI BIDANG PERTANIAN DALAM MENSEJAHTERAKAN MASYARAKAT MISKIN DI KABUPATEN KEPULAUAN TALAUD - BANDIL, ALFA; RUMAPEA, PATAR; PLANGITEN, NOVVA (Sam Ratulangi University, 2018)
Abstract: The welfare of the community is one of the goals expected by every region is no exception for theTalaud Island Regency various efforts are designed and implemented by the local Government solely to promotegrowth for the region itself and then expected to have a positive impact on the welfare of the community. Whilethe welfare of poor people in Talaud Island Regency is still now seen from the income of the community that issmall based on data in Central Bureau of Statistics of Talaud island Rehency. Local Government throughAgricultural Service of Agriculture of Talaud Island Regency create and implement program of empowermentof poor society working as farmer where community empowerment is done by forming group of farmer withhofe of existence of group of farmer this can improve prosperity of society which categorized as poor society.This research uses data collection technique that is descriptive research through technique of data collectionthat is observation, interview, anda documention. With data analysis techniques namely data reduction, datapresentation and conclusion. The fidings of this study indicate that the various agricultural assistance providedby the Local Government to be distributed to the poor through astablished farmer groups has had a good enoughimpact for the poor. Trough the assistance provided at least the level of income and and walfare of the poorhave started to rise to a better level than before, although not all poor people feel the help given by the LocalGovernment due to various limitations experienced by the Local Government one of then is the limited fundsso that the process of providing assistance in the field of agricultura is not given fully to the poor but is graduallygranted to the community throught a predetermined procedure.Keywords : Local Government, Policy, Agriculture